UJI AKTIVITAS ANTIBAKTERI EKSTRAK KULIT BUAH KAWISTA (LIMONIA ACIDISSIMA) TERHADAP ESCHERICHIA COLI - Putu Rika rika Veryanti; Ika Maruya Kusuma (Meditory : The Journal of Medical Laboratory, 2020)
Escherichia coli is a normal bacteria lives in the large intestine to help the process and maintain human digestive health. However, there are certain types of Escherichia coli which are pathogenic to human body and cause infections, such as diarrhea, urinary tract infections, meningitis, sepsis and so on. Irrational use of antibiotics leads to bacterial resistance to antibiotics. Kawista is one of the fruits that used as traditional medicine in Indonesia. Kawista peel extract can be used as an alternative therapy to prevent resistance. Based on the content of secondary metabolites, kawista peel extract is thought to have antibacterial activity. The purpose of this study was to determine the antibacterial activity of kawista (Limonia accidisima) peel extract against Escherichia coli. This research is an in-vitro study, preceded by a phytochemical screening test for methanol extract of kawista peel, then followed by an antibacterial activity test using the disc diffusion method and determining the minimum inhibitory concentration (MIC). The results showed that the kawista peel extract contained secondary metabolites such as alkaloids, flavonoids, saponins, tannins and terpenoids which have antibacterial activity. The concentration of the extract is directly proportional to its antibacterial activity. The 5% extract concentration gave an average inhibition zone diameter of 8.81 mm (moderate antibacterial activity), while at the 80% extract concentration the average inhibition zone diameter was 22.71 mm (very strong bacterial activity). Kawista peel extract (Limonia acidissima) has antibacterial activity with a minimum inhibitory concentration of 5%. Keywords: Antibacterial, Kawista, Limonia acidissima, Escherichia coli